ANALISIS KETERKAITAN PERUBAHAN LAHAN PERTANIAN TERHADAP KETAHANAN PANGAN KABUPATEN MAGELANG BERBASIS MODEL SPATIO TEMPORAL SIG - Rifki Destianto; Bitta Pigawati (Geoplanning: Journal of Geomatics and Planning, 2014)
As mandated by the 1945 Constitution of the Republic of Indonesia, agricultural land is part of the earth as a gift from God that is controlled by the state and utilized for the prosperity and welfare of the people. The agricultural land can provide great benefits in terms of economic, social, and environmental benefits. Land use conversion from agricultural to non-agricultural use can cause productivity decrease in agriculture, so it triggers a hypothesis that the decrease of agricultural land will negatively affect food security. Based on the problem, the research is conducted to assess the relationship between conversion in agricultural land use with food security using a case study of Magelang Regency (Kabupaten) in the 2009-11 period. The methods used are spatio-temporal GIS, quantitative analysis, and field calibration. The results have shown that the agricultural land area has decreased (6.31%) but the food security has not declined. It is because the food sources for Magelang Regency come from several adjacent areas. It can then be concluded that the reduction of agricultural land does not significantly affect the food security status of the study area. However, in the long run the decrease of the agricultural land will affect national food security. So, to maintain food security, agricultural land use control is necessary to prevent the unnecessary conversion of agricultural land.